2019
DOI: 10.1080/09602011.2019.1702561
|View full text |Cite
|
Sign up to set email alerts
|

Emotional adjustment post-stroke: A qualitative study of an online stroke community

Abstract: Understanding of emotional adjustment after stroke is limited. Under one-third of stroke survivors reporting emotional problems receive support. The aim of this study was to explore the process of emotional adjustment post-stroke and investigate the role played by participation in an online stroke community. We applied thematic analysis to 124 relevant posts within 114 discussion threads, written by 39 survivors and 29 carers. The contribution of online community engagement to emotional adjustment was explored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 37 publications
(44 reference statements)
0
14
0
Order By: Relevance
“…participating in a hobby at home by oneself ). For example, highly socialized activities provide a larger, welcoming community of social support that shares understanding of and provides aid to the stroke survivor beyond a caregiver or family unit ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…participating in a hobby at home by oneself ). For example, highly socialized activities provide a larger, welcoming community of social support that shares understanding of and provides aid to the stroke survivor beyond a caregiver or family unit ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“… 43 One study evaluated an online moderated discussion forum open to stroke patients and informal caregivers aimed to facilitate communication between these, and to share information about any aspects of stroke; the forum was hosted by a stroke survivors association and not moderated by professionals. 44 …”
Section: Resultsmentioning
confidence: 99%
“… 36 , 40 , 41 Another study found that increased mastery and social support gained using a website were significantly correlated with reduced depression of stroke survivors (respectively r = −0.49: P < 0.005, and r = −0.37; P < 0.05) at one month. 42 In addition, the qualitative study reported by Smith et al 44 characterized the process of emotional adjustment after stroke and the role of the online forum in this process. The authors found that participating in an online stroke community as a stroke survivor could be beneficial for the progression of positive emotional adjustment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This qualitative research with a virtual choir run for stroke survivors highlighted how these groups can provide a sense of belonging, but also the yearning of members to meet face‐to‐face and the limitations for those who are not able to use online technologies (Seckam & Hallingberg, 2021 ). Other research outside of the COVID‐19 pandemic shows how remote forms of contact between stroke survivors, such as online forums, can provide valuable emotional support post‐stroke (Smith et al, 2021 ). However, the current study was designed to extend this research to more broadly understand stroke survivors' experiences of perceived social support and shared social identity within stroke groups that would normally see and meet each other face‐to‐face (unlike online forums) but for a time are unable to do so.…”
Section: Peer‐support Groups In a Pandemicmentioning
confidence: 99%